Acoustics in the Division of Building Research - Warnock, A.C. C. (Canadian Acoustics, 1981)
The Noise and Vibration Section of the Division of Building Research (DBR) is concerned as the name suggests, with problems of acoustics and vibration as they relate to buildings. The work in the Section includes (1) studies of basic physical processes of propagation of sound and vibration in buildings; (2) studies of responses of people to sounds and vibration in their environment; and (3) the development of standard methods of measurement of the appropriate physical descriptors. The commitment, beyond research, is to apply the knowledge gained to the solution of specific building problems and to disseminate the information in appropriate form to designers, builders and the public.